Accreditation and Quality Assurance in Nigerian Tertiary Institutions: Challenges, Processes, and Implications for Educational Development - Hamidu Halilu; Umar Suleiman; Yusuf Benedict Garba (Goodwood Publishing, 2026)
Purpose: This study examines accreditation and quality assurance in Nigeria's tertiary education system, focusing on the challenges affecting the accreditation process and how they hinder its effectiveness in maintaining academic standards. Research methodology: This study adopts a descriptive and analytical approach, utilizing a review of relevant literature and policy documents to investigate the accreditation process, its challenges, and the impact of these factors on the quality of education in Nigerian universities, polytechnics, and colleges of education. Results: The findings highlight several challenges, including inadequate funding, a shortage of qualified academic staff, poor infrastructure, the politicization of the accreditation process, corruption, weak monitoring, and rapid institutional expansion. These factors significantly hinder the effectiveness of the accreditation process and its ability to ensure academic quality. Conclusions: Although accreditation remains a crucial mechanism for maintaining academic standards, its effectiveness in Nigeria is severely constrained by systemic and institutional factors. These challenges call for urgent policy and administrative reforms, including improved funding, better infrastructure, and stronger monitoring mechanisms, to enhance the accreditation process and ensure that it functions as intended. Limitations: This study primarily focuses on the challenges in the accreditation process within Nigeria’s tertiary education system and may not fully address solutions or offer a comparative perspective with other countries' systems. Contributions: This study contributes to the understanding of the critical role of accreditation in Nigeria’s higher education system and emphasizes the urgent need for reforms to improve the process and overall quality of education in the country.